Who’s Running the Show? Negotiating Control for Community Participation - Blasiola, Stacy; Carivou, James; Feng, Miao; Liu, Jun; Magee, Rachel; Sebastian, Melinda (AoIR Selected Papers of Internet Research, 2013)
As the internet and communication technologies have come to dominate daily life practices, the nuance in the complex relationships between social practices and the technologies that mediate them are sometimes obscured by the ability to aggregate. With the goal of getting at the heart of the nuance that shapes cultural participation, this paper session highlights the qualitative analysis of communities that emerge through the affordances of communication technologies. Ranging from political communities in China to cultural communities of fandom, each of these papers asks how everyday users employ tactics of resistance and/or appropriation to negotiate a digital space for their collective voices.Perhaps the most illustrative example of Twitter as a site of resistance was the Arab Spring. But in addition to its ability to mobilize political actors, Twitter affords opportunities for more subtle cultural power struggles. When the lights went out in the Superdome for Super Bowl XLVII, for example, Twitter erupted. During the blackout, users generated a staggering 285,000 tweets per minute—more than at any other point during the game. An analysis of tweets containing the #Lightsout hashtag revealed an interested trend: pop culture references. Interestingly, these tweets renegotiated the Super Bowl narrative as a form of storytelling—specific to their referenced pop culture text—under the shared theme of a hashtag. #Lightsout allowed potentially marginalized “Geek culture” communities to appropriate the Super Bowl narrative away from the classic machismo, consumerist rhetoric to one of their own.In China, as the tightening of state control over the mass media persists, people are left with only limited or no access to mass media and a mass-mediated public sphere. Yet China has both the world’s most active social network population and the world’s largest online population. How—and to what extent—are everyday use of new media articulating Chinese people’s experiences and shaping their social memory? An analysis of Weibo (China’s equivalent of Twitter) tweets from cities that were sites of collective action shows that Chinese social media provide people an alternative communicative sphere for sharing and accumulating “unofficial” social memory as a kind of covert resistance.While the #Lightsout and Weibo examples both highlight the potentially empowering effects of media technologies, the labor of contribution is not without its costs. On television websites and blogs, fans actively engage in the act of recapping—crafting a summary of a television show episode. Once a playful expression of fandom, the pressure to produce fresh, witty content in a timely manner challenges the play aspect of the activity. An analysis discusses the ways in which the recap can serve as an example of the tension inherent to convergence culture, where emphasis on the production and circulation of media content depends heavily on the participation of the consumer.As fans have reached out to media producers through the likes of recaps and roleplayers, to name a few methods, many media outlets are now actively reaching back to their fans through show and character specific Twitter accounts. This work studies the tweets from five television show accounts (The Americans, Breaking Bad, FaceOff, Grimm, and House of Cards) to characterize the way they interact with their fans and promote their shows. Findings indicate these shows use a variety of practices to encourage fan anticipation of new episodes and seasons, as well as participation in the story or fan group. Anticipation is supported through content sharing, countdowns, and discussions of watching styles, while participation focused practices include interaction with fans and performers/producers, use of insider knowledge and humor, and explicit calls for participation.Drawings from a wide range of topics, these papers highlight how resistance, and/or appropriation of narratives or technologies contribute to the complexity of social practices.